5, 7-Dibromo-8-hydroxyquinoline dissolved in binary aqueous co-solvent mixtures of isopropanol, N, N-dimethylformamide, 1, 4-dioxane and N-methyl-2-pyrrolidone: Solubility modeling, solvent effect and preferential solvation. (September 2020) - Zhu, Changfei; Farajtabar, Ali; Wu, Jiaxin; Zhao, Hongkun
Graphical abstract: Highlights: 5, 7-Dibromo-8-hydroxyquinoline solubility in four aqueous mixtures was determined and correlated. Preferential solvation of 5, 7-dibromo-8-hydroxyquinoline were derived through IKBIs method. Solvent effect was studied in terms of solvent-solvent and solute-solvent interactions. Abstract: The solubility of 5, 7-dibromo-8-hydroxyquinoline in four co-solvent mixtures of isopropanol + water, N, N -dimethylformamide (DMF) + water, N -methyl-2-pyrrolidone (NMP) + water and 1, 4-dioxane + water was acquired through the saturation shake-flask method at temperatures from 288.15 to 333.15 K. The solubility magnitudes were maximum in the neat solvents of DMF (isopropanol, NMP or 1, 4-dioxane) for the four co-solvent mixtures. The 5, 7-dibromo-8-hydroxyquinoline solubility was correlated very well with the help of the Jouyban-Acree model and van't Hoff-Jouyban-Acree model, obtaining relative average deviations less than 6.07% and root-mean-square deviations less than 4.81 × 10 −4 . The local mole fractions of isopropanol (DMF, NMP or 1, 4-dioxane) and water nearby the 5, 7-dibromo-8-hydroxyquinoline were quantitatively evaluated through the method of Inverse Kirkwood–Buff integrals. 5, 7-Dibromo-8-hydroxyquinoline was preferentially solvated by water for these mixtures in water-rich compositions; while within intermediate and co-solvent-rich compositions, 5, 7-dibromo-8-hydroxyquinoline was preferentially solvated by isopropanol (DMF, NMP or 1, 4-dioxane). Additionally, the Kamlet and Taft linear solvation energy relationships were used to rationalize the solvent effect on the solubility. Results indicated that the variation of solubility was mainly governed by the change in cavity formation energy in all the aqueous mixtures.